1973
DOI: 10.1111/j.2044-8295.1973.tb01369.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Exploratory Behaviour and Fear: A Review

Abstract: Two main theories of the relationship between exploratory behaviour and anxiety or fearfulness are: (a) ‘Two‐factor theory’, according to which novel stimuli evoke both curiosity and fear/anxiety, with exploration as the outcome of competing tendencies to approach and avoid, and (b) the ‘Halliday‐Lester theory’, where the fear aroused by novelty results in either approach (low fear) or avoidance (high fear). Relevant evidence comes from animal studies varying fear by manipulating either environmental or intrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
53
0
2

Year Published

1974
1974
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(55 citation statements)
references
References 0 publications
0
53
0
2
Order By: Relevance
“…In a test of free exploratory behavior, BALB͞c mice were placed in a large unfamiliar environment (23)(24)(25). Exploration was measured in activity monitors (40 ϫ 40 ϫ 30 cm, Omnitech Electronics, Columbus, OH) placed in a soundproof room with no light.…”
mentioning
confidence: 99%
“…In a test of free exploratory behavior, BALB͞c mice were placed in a large unfamiliar environment (23)(24)(25). Exploration was measured in activity monitors (40 ϫ 40 ϫ 30 cm, Omnitech Electronics, Columbus, OH) placed in a soundproof room with no light.…”
mentioning
confidence: 99%
“…These data show that the effect of lesions of the amygdala and related structures on exploration are different when different types of exploration are measured. The role of the amygdala and its afferent and efferent neural connections in mediating the two types of exploration studied is discussed.Although exploration by rats has been studied extensively at the behavioral level (Barnett, 1963;Barnett & Cowan, 1976;Fowler, 1965;Halliday, 1968;Lester, 1968;McReynolds, 1962;Russell, 1973), relatively little is known about the affective processes and the related neural substrates which mediate this behavior. Exploration is usually discussed in relation to emotionality in general, and to such anthropomorphic concepts as "fear" and "curiosity" in particular (Blanchard & Blanchard, 1972;Blanchard, Kelley, & Blanchard, 1974;Montgomery, 1955;Montgomery & Monkman, 1955).…”
mentioning
confidence: 99%
“…Exposure to a novel environment for a continuous period or for several discrete periods will, in general, result in a gradual decrease of locomotor activity over the course of several days or weeks (Russell, 1973;Warren and Callaghan, 1976;Clark and Ehlinger, 1987). Novelty represents a potentially stressful situation (Russell, 1973;Csányi and Tóth, 1985;Gervai and Csányi, 1986).…”
Section: Interpretation Of Fish Locomotion With Nonlinear Measuresmentioning
confidence: 99%
“…Novelty represents a potentially stressful situation (Russell, 1973;Csányi and Tóth, 1985;Gervai and Csányi, 1986). For example, male guppies initially show high velocity swimming at the periphery of an open field, and it has been suggested that this activity is related to some degree of fear (Warren and Callaghan, 1976).…”
Section: Interpretation Of Fish Locomotion With Nonlinear Measuresmentioning
confidence: 99%